TRACING TEXTILE PRODUCTION FROM THE VIKING AGE TO THE MIDDLE AGES tools, textiles, texts and... contexts. - OYE, INGVILD (OXBOW BOOKS, 2022)
"This book concerns textile production at the fringes of north-western Europe - areas in western Norway and the North Atlantic in the expanding, dynamic and transformative period from the early Viking Age into the Middle Ages. Textiles constitute one of the basic needs in human life - to protect and keep the body warm but also to show social status and affiliations. Textiles had a wide spectrum of use areas and qualities, fine and coarse in various contexts, and in the Viking Age not least related to the production of sails - all essential for the development and character of the period. So, what were the tools and textiles like, who made them, who used them and who exposed them? By tracing textile production from the remains of tools and textiles in varied landscapes and settings - Viking-Age graves and in situ workplaces from the whole period - and combining this with textual insights, many layers of information are exposed about technology and qualities as well as gender, gender roles, social relations, power and networks. By combining tools, textiles and texts in various settings, this book contextualises dispersed archaeological finds of tools and textiles to uncover patterns across larger areas and in a long-term perspective of half a millennium"--